Evaluative Lessons for Agriculture and Agribusiness - Evaluation Cooperation Group (World Bank, Washington, DC, 2017)
Agricultural investments made by developing countries and multilateral development banks (MDBs) have declined in recent decades. This decline is associated with a slowdown in the growth of agriculture productivity. Most development institutions have recognized the damage caused by this past neglect, in part evident in rising food prices, and renewed attention to agriculture and agribusiness is emerging. But this renewed interest will need to deliver results, especially in Sub-Saharan Africa, where the MDBs have had the least success but where the needs and opportunities are enormous. This paper synthesizes recent work by the independent evaluation agency members of the Evaluation Cooperation Group (ECG) and incorporates lessons from related research by MDBs and from the academic literature on agriculture and agribusiness. The objectives of the paper, in addition to distilling evaluative lessons for agriculture and agribusiness, are to examine the key constraints on the sector and to provide evaluators, operational staff, and policy makers with an evaluative perspective on interventions in countries at different stages of development.